Integrative genomics analysis of genes with biallelic loss and its relation to the expression of mRNA and micro-RNA in esophageal squamous cell carcinoma. (December 2015) - Hu, Nan; Wang, Chaoyu; Clifford, Robert; Yang, Howard; Su, Hua; Wang, Lemin; Wang, Yuan; Xu, Yi; Tang, Ze-Zhong; Ding, Ti; Zhang, Tongwu; Goldstein, Alisa; et al.
Abstract Background Genomic instability plays an important role in human cancers. We previously characterized genomic instability in esophageal squamous cell carcinomas (ESCC) in terms of loss of heterozygosity (LOH) and copy number (CN) changes in tumors. In the current study we focus on biallelic loss and its relation to expression of mRNA and miRNA in ESCC using results from 500K SNP, mRNA, and miRNA arrays in 30 cases from a high-risk region of China. Results (i) Biallelic loss was uncommon but when it occurred it exhibited a consistent pattern: only 77 genes (<0.5 %) showed biallelic loss in at least 10 % of ESCC samples, but nearly all of these genes were concentrated on just four chromosomal arms (ie, 42 genes on 3p, 14 genes on 9p, 10 genes on 5q, and seven genes on 4p). (ii) Biallelic loss was associated with lower mRNA expression: 52 of the 77 genes also had RNA expression data, and 41 (79 %) showed lower expression levels in cases with biallelic loss compared to those without. (iii) The relation of biallelic loss to miRNA expression was less clear but appeared to favor higher miRNA levels: of 60 miRNA-target gene pairs, 34 pairs (57 %) had higher miRNA expression with biallelic loss than without, while 26 pairs (43 %) had lower miRNA expression. (iv) Finally, the effect of biallelic loss on the relation between miRNA and mRNA expression was complex. Biallelic loss was most commonly associated with a pattern of elevated miRNA and reduced mRNA (43 %), but a pattern of both reduced miRNA and mRNA was also common (35 %). Conclusion Our results indicate that biallelic loss in ESCC is uncommon, but when it occurs it is localized to a few specific chromosome regions and is associated with reduced mRNA expression of affected genes. The effect of biallelic loss on miRNA expression and on the relation between miRNA and mRNA expressions was complex.